Implementasi Model Pembelajaran Project Based Learning (PJBL) Untuk Meningkatkan Konsentrasi Belajar Mahasiswa Pada Matakuliah Pembelajaran Sains SD - M.Nur, Faizah; Tutiliana; Zainatul Hasanah; Rizki Aria (Jurnal Serambi Ilmu, 2025)
This research aims to increase the learning concentration of students in the third semester of the PGSD study program in the Science Learning course. The data collection method is carried out by interviews and direct observation of the learning process in the classroom. The research technique of classroom action (PTKI) was carried out in two cycles with 5 meetings, namely cycle I and cycle II in accordance with the theory developed by Kemmis and mc.Taggart. The results of the study showed that in cycle I by varying teaching techniques by adding audio visual media obtained results of 63% The average level of student learning concentration, out of 30 students there were 10 students who were still very lacking in learning concentration. This shows that the learning process has not been successful in cycle I, therefore the researcher continues to cycle II, the researcher has applied the PJBl model and obtained an increase in student learning concentration seen from each indicator studied. The data produced in the second cycle was 83% of the average student learning concentration. This shows that the use of the PjBl model in increasing student learning concentration consistently has been tested.